2020
DOI: 10.15388/20-infor398
|View full text |Cite
|
Sign up to set email alerts
|

Voice Activation Systems for Embedded Devices: Systematic Literature Review

Abstract: A large number of modern mobile devices, embedded devices and smart home devices are equipped with a voice control. Automatic recognition of the entire audio stream, however, is undesirable for the reasons of the resource consumption and privacy. Therefore, most of these devices use a voice activation system, whose task is to find the specified in advance word or phrase in the audio stream (for example, Ok, Google) and to activate the voice request processing system when it is found. The voice activation syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Present 7% of error by implementing time series normalized difference vegetation index which is obtained from MODIS. The authors in [22] presented a new approach for estimating the crop yield through to the temperature vegetation dryness index by computing the RMSE coefficients in range between 10% to 14% for soybean and 15% to 23% for wheat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Present 7% of error by implementing time series normalized difference vegetation index which is obtained from MODIS. The authors in [22] presented a new approach for estimating the crop yield through to the temperature vegetation dryness index by computing the RMSE coefficients in range between 10% to 14% for soybean and 15% to 23% for wheat.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors compared multilingual bottleneck features of the model, trained on well-resourced, but out-of-domain languages, and a correspondence autoencoder trained in a zero-resource fashion, as well as their combination. They found that this combination improves the quality of the voice activation system compared to the Mel-frequency cepstral coefficients (MFCC), which are widely used in ASR and voice activation [1].…”
Section: Low-resource Abstractpottingmentioning
confidence: 99%
“…The log-Mel filter banks features are often chosen for building voice activation or speech recognition systems [1,32]. We used the kaldi [33] implementation of feature computation with the following parameters: frame width-25 ms, frame shift-10 ms, number of bins-80.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Siūloma tipinės balso aktyvavimo sistemos apžvalga ir struktūra buvo paskelbta tarptautiniame mokslo žurnale (Kolesau & Šešok, 2020c).…”
Section: Ginamieji Teiginiaiunclassified